Some characteristics of primary and secondary school geographical education in Maribor - Konečnik Kotnik, Eva; Petauer, Milena (Journal for Geography, 2006)
Our research deals with the situation of geographical education in primary and secondary schools in Maribor. Special attention has been paid to the situation of geography in the syllabuses of primary and secondary schools in the region of Maribor. The specificity of the subject geography in the stated region is described on the basis of the analysis of participating in geographic competitions, by means of establishing the research orientation of field work and excursions, and by means of the analysis of the co-operation of primary and secondary schools of Maribor with the Department of Geography at the Pedagogic Faculty of the University of Maribor.